Clinical outcome of patients with obscure gastrointestinal bleeding during antithrombotic drug therapy. (12th January 2018) - Kono, Yoshiyasu; Kawano, Seiji; Okamoto, Yuki; Obayashi, Yuka; Baba, Yuki; Sakae, Hiroyuki; Abe, Makoto; Gotoda, Tatsuhiro; Inokuchi, Toshihiro; Kanzaki, Hiromitsu; Iwamuro, Masaya; Kawahara, Yoshiro; et al.
Background: The clinical outcome of patients with obscure gastrointestinal bleeding (OGIB) during antithrombotic drug therapy has not been fully investigated. Methods: Patients who underwent video capsule endoscopy (VCE) for the investigation of OGIB at Okayama University Hospital from January 2009 to March 2016 were enrolled. We evaluated the VCE findings, the patterns of OGIB, and the rate of rebleeding within 1 year in antithrombotic drug users and antithrombotic drug nonusers. Results: A total of 181 patients were enrolled. Among the antithrombotic drug users, the rate of VCE positivity in the patients with overt OGIB was significantly higher in comparison with patients with occult OGIB (45% versus 16%, p = 0.014), whereas there was no significant difference among the antithrombotic drug nonusers (27% versus 26%, p = 1.0). Among the antithrombotic drug users, the rate of rebleeding among the VCE-positive patients was significantly higher in comparison with the VCE-negative patients (50% versus 5.9%, p = 0.011). Moreover, among antithrombotic drug users who did not receive therapeutic intervention, the rate of rebleeding among the VCE-positive patients was significantly higher in comparison with the VCE-negative patients (75% versus 6.3%, p = 0.001). However, among the antithrombotic drug nonusers who did not receive therapeutic intervention, the rebleeding rate of the VCE-positive patients was not significantly different from that of the VCE-negative patients (20% versus 9.4%, p = 0.43). Conclusion: Therapeutic intervention should be considered for patients with overt OGIB who are VCE positive and who use antithrombotic drugs due to the high risk of rebleeding.